PEMBERDAYAAN FUNGSI MASJID MELALUI PENDEKATAN SOCIAL ENTERPRENEURSHIP - Zeni Lutfiyah; Sholikhah Sholikhah; Junaidi Junaidi (Journal of Law, Society, and Islamic Civilization, 2017)
This program aims to increase public awareness in managing the function of mosque for the purpose of doing social change especially in economic field through Zakat, Infak, Shodaqoh and Wakaf (Ziswaf) fund. In addition, with this dedication is expected to build coordination and synergy of community empowerment programs undertaken by PSEI UNS Surakarta with that mosque prgram. While the target of this devotion is to facilitate the development of empowerment of mosque functions in each mosque assisted. The method applied in this program is Participatory Rural Appraisal (PRA) which prioritizes critical dialogue by way of subject-based disclosure, so as to obtain a real perspective in the mind of the target subject and at the same time fulfill the paradigmatic alignment as mentioned above. The approach taken in this program is the approach of social entrepreneurship, which combines the increase in the value of resources economically as well as streamline social goals and mission. This approach has the goal of improving social aspects, as well as implementing an integrated strategy between social and economic aspects.Keywords : enpowermen, mosque, entrepreneurshipPengabdian ini bertujuan meningkatkan kepedulian masyarakat dalam mengelola fungsi masjid untuk tujuan melakukan perubahan sosial terutama di bidang ekonomi melalui dana Zakat, Infak, Shodaqoh dan Wakaf (Ziswaf). Di samping itu juga dengan pengabdian ini di harapkan bisa membangun koordinasi dan sinergi program pemberdayaan masyarakat yang dilakukan PSEI UNS Surakarta dengan program pemberdayaan di Masjid dampingan. Sedangkan target pengabdian ini adalah menfasilitasi pengembangan pemberdayaan fungsi masjid di setiap masjid dampingan. Metode yang diterapkan dalam program ini adalah Participatory Rural Appraisal (PRA) yang mengutamakan dialog kritis dengan cara pengungkapan berbasis subyek dampingan, sehingga diperoleh perspektif yang nyata dalam fikiran subyek dampingan dan sekaligus memenuhi keselarasan paradigmatik sebagaimana disampaikan di atas. Adapun pendekatan yang dilakukan dalam program ini adalah pendekatan social entrepreneurship (kewirausahaan sosial) yang mengkombinasikan peningkatan nilai sumberdaya secara ekonomis sekaligus mengefektifkan tujuan dan misi sosial. Pendekatan ini memiliki tujuan peningkatan aspek social, serta menerapkan strategi terintegrasi antara aspek sosial dan ekonomi.Kata Kunci; pemberdayaan, masjid, kewirausahaan